Protection of Children Victims of Criminal Offences in (Pre)Criminal Procedure (Zaščita otrok žrtev kaznivih dejanj v (pred)kazenskem postopku) - Dajana Janjatović (Zbornik Znanstvenih Razprav)
The issue of secondary victimisation of children victims of criminal offences because of their participation in the (pre)criminal procedure has long been the subject of discus-sions within the victimological community. Protective measures, and legislation reforms related thereto, play a key role in creating a child-friendly justice system, however, they are often too slow, inconsistent, or insufficiently implemented in practice. This discus-sion deals with the development, good practices, and shortcomings of Slovenian legisla-tive solutions in the field of protection of children victims of criminal offences in (pre)criminal procedures.